2020
DOI: 10.3390/ijms21249409
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Mediated Autophagy by Ursolic Acid Inhibits Growth and Metastasis of Esophageal Cancer Cells

Abstract: Ursolic acid (UA) possesses various pharmacological activities, such as antitumorigenic and anti-inflammatory effects. In the present study, we investigated the mechanisms underlying the effects of UA against esophageal squamous cell carcinoma (ESCC) (TE-8 cells and TE-12 cells). The cell viability assay showed that UA decreased the viability of ESCC in a dose-dependent manner. In the soft agar colony formation assay, the colony numbers and size were reduced in a dose-dependent manner after UA treatment. UA ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…Numerous studies have reported that UA regulates the apoptosis, proliferation, metastasis, and cell cycle of different cancer cells through several signaling pathways, including Akt/PI3K [ 28 , 29 ], NF-Κβ [ 27 ], and STAT3 [ 26 , 78 ]. In agreement with those studies, our previous study showed that UA effectively inhibited cell viability and induced ROS-mediated autophagy in esophageal cancer cells through the Akt/mTOR signaling pathway [ 31 ], suggesting that UA might act as a potential anti-tumor reagent in esophageal cancer. Although PTX shows significant efficacy as a common esophageal cancer chemotherapy drug, chemo-resistance reduces its effects [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Numerous studies have reported that UA regulates the apoptosis, proliferation, metastasis, and cell cycle of different cancer cells through several signaling pathways, including Akt/PI3K [ 28 , 29 ], NF-Κβ [ 27 ], and STAT3 [ 26 , 78 ]. In agreement with those studies, our previous study showed that UA effectively inhibited cell viability and induced ROS-mediated autophagy in esophageal cancer cells through the Akt/mTOR signaling pathway [ 31 ], suggesting that UA might act as a potential anti-tumor reagent in esophageal cancer. Although PTX shows significant efficacy as a common esophageal cancer chemotherapy drug, chemo-resistance reduces its effects [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…UA can prevent cancer through many signaling pathways, such as ROCK/PTEN, TGF-β1/ZEB1, and MAPK/ERK signaling [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In addition, UA induces cell death with autophagy in patients with esophageal cancer [ 31 ]. Therefore, it seems necessary to study various functions of UA in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…(Castrejon-Jimenez et al, 2019). Similarly, UA is also reported to inhibit metastasis of esophageal cancer cells by ROS-mediated autophagy (Lee et al, 2020). Additionally, UA induces apoptosis and inhibits autophagy progression, leading to PC-12 cell death (Jung et al, 2018).…”
Section: Ursolic Acidmentioning
confidence: 96%
“…Analysis of data from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases found that colon adenocarcinoma patients have increased expression of cyclin B1 that acts as a tumor promoting gene, and this overexpression can be reversed with treatment of ursolic acid in HCT-116 and SW-480 cells [107]. A number of other studies have demonstrated that ursolic acid has anti-cancer effects against various cancer types including esophageal cancer [108], pancreatic cancer [109], and colorectal cancer [110] via a number of different mechanisms, including the induction of ROS-mediated autophagy [108] and ER stressmediated RAGE inhibition, promoting apoptosis and autophagy [109], and up-regulation of ROS and caspase-3, -8, and -9, thereby inducing apoptosis [92]. Further anti-tumor effects of ursolic acid have been observed in papillary thyroid carcinoma cells, mediated via enhancement of fibronectin-1 expression and subsequent induction of apoptosis [111].…”
Section: Ursolic Acidmentioning
confidence: 99%